Home
О нас
Products
Services
Регистрация
Войти
Поиск
leonidbystrizkij
@leonidbystrizkij
June 2023
1
6
Report
Помогите решить эти 2 задания . Спасибо огромное)
Please enter comments
Please enter your name.
Please enter the correct email address.
Agree to
terms of service
You must agree before submitting.
Send
Answers & Comments
lerapion
7.х-5/х-3=х/х+1
(х-5)(х+1)=х(х-3)
х^2+х-5х-5=х^2-3х
х^2+х-5х-х^2+3х=5
-х=5
х=-5
8.7х/8х^2-98 : (2х-7)^2-(2х+7)^2/(2х+7)(2х-7)= 7х/8х^2-98 : -14•4х/(2х+7)(2х-7)=
7х/8х^2-98 : -56х/(2х+7)(2х-7)=-7х/2(2х-7)(2х+7)•(2х-7)(2х+7)/56х=-1/2•1/8=-1/16
-1/16=-1/16- тотож. доведено
1 votes
Thanks 1
More Questions From This User
See All
leonidbystrizkij
July 2023 | 0 Ответы
fed5ca31067f45b186d377f75778f8c7
Answer
leonidbystrizkij
June 2023 | 0 Ответы
i i 15 i i
Answer
leonidbystrizkij
June 2023 | 0 Ответы
fb0599afe5c5e4118a3909ac9abf4912
Answer
leonidbystrizkij
June 2023 | 0 Ответы
2e884a64a0593f6833d1237865c27bf8
Answer
leonidbystrizkij
November 2022 | 0 Ответы
92 python def float if else
Answer
×
Report "Помогите решить эти 2 задания . Спасибо огромное)"
Your name
Email
Reason
-Select Reason-
Pornographic
Defamatory
Illegal/Unlawful
Spam
Other Terms Of Service Violation
File a copyright complaint
Description
Helpful Links
О нас
Политика конфиденциальности
Правила и условия
Copyright
Контакты
Helpful Social
Get monthly updates
Submit
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
(х-5)(х+1)=х(х-3)
х^2+х-5х-5=х^2-3х
х^2+х-5х-х^2+3х=5
-х=5
х=-5
8.7х/8х^2-98 : (2х-7)^2-(2х+7)^2/(2х+7)(2х-7)= 7х/8х^2-98 : -14•4х/(2х+7)(2х-7)=
7х/8х^2-98 : -56х/(2х+7)(2х-7)=-7х/2(2х-7)(2х+7)•(2х-7)(2х+7)/56х=-1/2•1/8=-1/16
-1/16=-1/16- тотож. доведено